Phenophasic heat units requirement and growth variations of safflower (Carthamus tinctorius L.) varieties under different sowing dates: PHENOPHASIC HEAT UNITS AND GROWTH VARIATIONS OF SAFFLOWER UNDER DIFFERENT SOWINGS - S V KHADTARE; S K SHINDE; V M TORADMAL (Journal of Oilseeds Research, 2018)
The field experiment was conducted at the dry farming research station, Solapur having three different sowing dates and seven varieties of safflower. Early sown safflower requires 7-9 days more for attaining physiological maturity than latest sown safflower. Among the varieties, SSF-708 was found significantly more efficient over other genotypes in duration and yield. The deviation in heat unit requirement among early and late sown safflower due to sowing dates was